Behind the veil [videorecording] voices of Moro women - Philippine Center for Investigative Journalism ([Quezon City] Philippine Center for Investigative Journalism, 1998)
Three decades of war have caused untold anguish to Bangsamoro women. But they have remained resolute and strong. Now they face a dilemma.
War is bloody and costly, and peace does not always right old wrongs. As they contemplate their situation. Bangsamoro women hold on to Islam. The veil is the symbol of their commitment to their people and their way of life. It is the mark of their faith.
Summary taken from container
Executive Producer: Luz Rimban; Field Producer/Director: Jam Bonoan; Writer: Jo-An Maglipon;Narrator: Ma. Socorro Diokno; Photos: Luz Rimban
Keywords: Moro National Liberation Front; Bangsamoro Women Foundation for Peace and Development; Moro Islamic Liberation Front; Muslim women; Bangsamoro women -- Philippines -- Mindanao; Mindanao History -- Autonomy and independent Movement